THE ROLE OF MAMMALIAN DRUGS IN RELATION TO HEALTH CARE AMONG TRIBALS IN JHARKHAND (BIHAR) PART- I - AZMI, H.K.; PANDEY, PRABHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
During the course of medico-ethnozoological survey of Jharkhand area of Bihar covering 4 districts namely Dhanbad, Hazaribagh, Ranchi and Sathal Pargana, available informations with regard to the native use of medicinal mammals by the tribals in the treatment of human diseases have been recorded. The study has revealed the use of about 12 mammals in the treatment of various human ailments.